Lung and gut microbiota profiling in severe community acquired pneumonia patients: a prospective pilot study - Zou, Wei; Zheng, Ruobin; Lin, Sheng; Lu, Chunhua; Xie, Baosong (Frontiers in Microbiology, 2025)
BackgroundThe gut and lung microbiomes play crucial roles in host defense and may serve as predictive markers for severe community-acquired pneumonia (SCAP) patients. However, the simultaneous landscapes of lung and gut microbiomes for SCAP patients remain unclear. The primary objective of this research is to investigate the concomitant landscape of the lung and gut microbiota between the death group and the survival group of SCAP patients and to identify microbial features predictive of clinical parameters.MethodsWe analyzed 50 respiratory samples and 50 stool samples collected from 50 SCAP patients in this prospective observational study. Patients were categorized into the survival group (n = 41) and the death group (n = 9) according to clinical outcomes. We characterized microbiome compositions, LEfSe analysis, UPGMA analysis and correlation of microbiota features with clinical parameters of respiratory and intestinal flora between two groups using 16S rRNA gene sequencing.ResultsIn comparison with the survival group, the death group demonstrated a reduction in alpha diversity, most markedly reflected in the lung microbiota. We found enrichment of specific lung bacterial taxa (Bacteroidales, Streptococcus) in the survival group compared to the death group. Similarly, specific gut bacterial taxa (Anaerotruncus, Peptacetobacter, Rutheniibacterium) were also enriched in the survival group Our study revealed that lung bacteria such as Asteroleplasma, Campylobacter and Acinetobacter and intestinal bacteria such as Bifidobacterium, Ligilactobacillus, Veillonella, and Corynebacterium were positively correlated with inflammatory markers PCT or CRP or neutrophil percentage. Besides, lung bacteria such as Schaalia and intestinal bacteria Alistipes were positively correlated with PaO2/FiO2, while lung bacteria such as Stenotrophomonas was negatively correlated with PaO2/FiO2.ConclusionsOur findings reveal distinctive microbial profiles in lung and gut microbiota that correlate with clinical outcomes in SCAP patients. Unraveling these microbial patterns could enable targeted interventions to improve outcomes of SCAP patients.